POS (Perceived Organizational Support), Organizational Learning Culture (OLC) Terhadap OCB (Organizational Citizenship Behaviour) Melalui Job Satisfaction - Cindy Permata Sari; Salman Farisi (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study aims to determine the effect of POS (perceived Organizational Support), OLC (Organizational Learning Culture) on OCB (Organizational Citizenship Behaviour) through Job Satisfaction on 106 employees at PT Telkom Indonesia Tbk Telkom Medan Region, Indonesia. The data analysis method uses the Partial Least Square (PLS) method. The results showed that Pos (Perceived Organizational Support) and Job Satisfaction had a significant positive effect, Olc (Organizational Learning Culture) and Job Satisfaction had a significant positive effect, Pos (Perceived Organizational Support) and OCB (Organizational Citizenship Behaviour) had no significant effect, Olc (Organizational Learning Culture) and OCB (Organizational Citizenship Behaviour) had a significant positive effect, Job Satisfaction and OCB Organizational Citizenship Behaviour have a positive and significant effect, POS (Perceived Organizational Support) on OCB (Organizational Citizenship Behaviour) through Job satisfaction is negatively insignificant, Olc (Organizational Learning Culture) on OCB (Organizational Citizenship Behaviour) through Job satisfaction is negatively insignificant. Keywords: POS (perceived organizational support), OLC (organizational learning culture), OCB (organizational citizenship behavior), job satisfaction.